The use of piezoelectric instrumentation and platelet rich fibrin matrix in septorhinoplasty: report of two cases - Dimić, Aleksandar; Stojiljković, Vladimir; Vujačić, Tamara (Vojnosanitetski pregled, 2022)
Introduction. Rhinoplasty is one of the most commonly performed surgeries in the area of aesthetic surgery. Surgical instruments, which are used in traditional rhinoplasty, like saws, chisels and osteotomes are relatively imprecise and their usage can lead to uncontrolled fractures of the bone and consequently to inadequate final results. Piezoelectric-powered ultrasonic instruments (PEI) are currently the most innovative instrumentation available for minimally traumatic reshaping of the bony vault and lateral walls. There are many studies which have shown positive effects of platelet-rich fibrin (PRF) in postoperative course of rhinoplasty patients. Case report. We presented two innovative approaches in rhinoplasty combined PEI and PRF matrix through two case reports. In both patients, satisfying results were achieved by use of PEI technique. Also, usage of PRF membrane provided good healing and small postoperative edema. Conclusion. Based on our experience, the use of of PEI technique has many benefits. It is safe, practical and effective method and it demonstrates valuable and favourable results in osteotomies. Also, usage of PRF membrane helps patients in better healing and less postoperative edema.